Cognitive skills, tasks and job mobility - Arne Jonas Warnke; Peer Ederer; Philipp Schuller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The authors investigate on the basis of primary and secondary data the relationship between individual cognitive skills and the complexity of the particular work those individuals perform. Additionally, the relationship between skills and mobility between more or less complex jobs in an highly homogenous industrial environment is analyzed. The primary data consists of a survey conducted in 2011 of anonymously tested 305 participants in selected factories of four different companies. The survey consists of a newly developed dynamic problem solving test and a standard general intelligence test. Skill measurement is supplemented by information about tasks and personal background. Results are compared to larger scale secondary data sources. Special focus is placed on different employment groups within a company: assemblers, craftsmen, technicians and engineers. Using this data, we can show that non-routine content of individual work is strongly related to cognitive skills. Also, higher cognitive skill levels predict upward occupational mobility. Finally, we demonstrate that the established task-based approach helps to explain why the occupational mobility between some occupational groups is lower than between others. These findings can be useful for the discovery of opportunities for occupational upward mobility in a homogenous environment.
Keywords: J24; J62; J60; 330